Development and initial validation of the comprehensive HIV adherence with treatment scale - Rahm-Knigge, Ryan L., author; Conner, Bradley T., advisor; Luong, Gloria, committee member; Harman, Jennifer J., committee member; Prince, Mark A., committee member (Colorado State University. Libraries, 2021)
HIV remains a significant public health concern despite decreasing rates of transmission in the U.S. (Centers for Disease Control and Prevention, 2020c). Contributing factors include low rates of treatment adherence (de Bruin et al., 2010) and high rates of comorbidities with other medical and mental health conditions (Bing et al., 2001; Gallant et al., 2017; Lerner et al., 2020). Antiretroviral therapy (ART) has significantly improved HIV health outcomes and reduced AIDS diagnoses and AIDS-related mortality (Crum et al., 2006; Glass et al., 2008; Ickovics & Meade, 2002; Paterson et al., 2000; Stone, 2001; World Health Organization, 2015). Because of ART's effectiveness, HIV is considered a chronic rather than terminal health condition for people adherent with treatment (Aberg, 2006; Swendeman, Ingram, & Rotheram- Borus, 2009). Treatment for HIV as a chronic health condition includes several pro-health behaviors in addition to ART adherence to support overall wellness. To support future research and treatment recommendations, the current study developed a measure of adherence with pro- health behavior and conducted an initial analysis of the measure's psychometric properties with a sample of 118 people living with HIV. Structural equation modeling explored relations among antecedents (personality, treatment self-efficacy, treatment information, and treatment motivation) and health outcomes of pro-health behaviors and ART adherence. Regularly assessing engagement in, as well as antecedents and outcomes of, treatment behaviors can enhance communication between providers and people living with HIV, reinforce HIV's status as a manageable chronic condition, and link people living with HIV to appropriate interventions.